Lived Experiences of Mothers Caring for Hemodialysis Patients: A Phenomenological Study - Espiritu, Eloisa May; Del Rosario, Maria Shane (International Journal of Sustainability and Advanced Integrated Research, 2026)
Mothers of hemodialysis patients face significant physical, emotional, and financial burdens as primary caregivers for individuals with end-stage renal disease. This study aimed to explore the lived experiences of mothers caring for hemodialysis patients in two private hospitals in the Philippines and to identify the psychosocial and financial challenges they encounter. A qualitative phenomenological research design was employed, involving six (6) mothers selected through purposive sampling from Amando D. Cope Memorial Hospital and Jaime B. Berces Memorial Hospital. Data were gathered through in-depth semi-structured interviews and analyzed using thematic analysis. Results revealed that mothers experienced profound emotional distress, including anxiety, depression, and feelings of isolation due to the demanding nature of caregiving. Psychosocial challenges included balancing multiple responsibilities, managing guilt and helplessness, and coping with limited social support systems. Financial burdens were substantial, with mothers reporting loss of income, increased out-of-pocket expenses for treatment and transportation, and long-term economic instability. Despite these challenges, mothers demonstrated resilience through faith, family support, and personal determination. The study concludes that mothers of hemodialysis patients require comprehensive support systems that address their emotional, social, and financial needs. Healthcare providers and policymakers must develop targeted interventions including accessible mental health services, financial assistance programs, caregiver education, and community-based support networks. The findings of this study provide valuable insights for improving the well-being of mothers and enhancing the quality of care provided to hemodialysis patients in the Philippines.
Keywords: Hemodialysis; Maternal Caregivers; Lived Experiences; Psychosocial Challenges; Financial Burden; Philippines